2020
DOI: 10.7150/ijbs.47203
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-based biomarkers, therapies, and resistance in Cancer

Abstract: MicroRNAs (miRNAs), small non-coding RNAs (ncRNAs) of about 22 nucleotides in size, play important roles in gene regulation, and their dysregulation is implicated in human diseases including cancer. A variety of miRNAs could take roles in the cancer progression, participate in the process of tumor immune, and function with miRNA sponges. During the last two decades, the connection between miRNAs and various cancers has been widely researched. Based on evidence about miRNA, numerous potential cancer biomarkers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
195
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(239 citation statements)
references
References 229 publications
(222 reference statements)
1
195
0
Order By: Relevance
“…In various contexts, a specific miRNA could simultaneously produce competing oncogenic and tumor suppressive effects by the modulation of oncogenic or tumor suppressive mRNAs, respectively [ 43 ]. Additionally, miRNAs can modulate tumor-modifying extrinsic factors such as cancer-immune system interactions, stromal cell interactions, and sensitivity to therapy [ 44 , 45 , 46 ]. It likely the balance between these processes which determines the net outcome of whether a specific miRNA produces an oncogenic or tumor suppressive effect.…”
Section: Discussionmentioning
confidence: 99%
“…In various contexts, a specific miRNA could simultaneously produce competing oncogenic and tumor suppressive effects by the modulation of oncogenic or tumor suppressive mRNAs, respectively [ 43 ]. Additionally, miRNAs can modulate tumor-modifying extrinsic factors such as cancer-immune system interactions, stromal cell interactions, and sensitivity to therapy [ 44 , 45 , 46 ]. It likely the balance between these processes which determines the net outcome of whether a specific miRNA produces an oncogenic or tumor suppressive effect.…”
Section: Discussionmentioning
confidence: 99%
“…Calin et al reported that more than 50% of miRNA genes are located in genomic regions associated with cancer 9 . It is now well established from a variety of studies that miRNAs are involved in tumor progression as oncogenes or tumor suppressors 10 , 11 . In addition, miRNAs also play essential regulatory roles in inflammatory and immune responses 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The miRNA microarray is one of the most common methods of screening disease-associated miRNAs, and several studies using this technology have revealed aberrant miRNA expression in human malignant tumors ( 10 , 29 ), including CRC ( 17 ). Volinia et al ( 29 ) used miRNA microarrays to study the expression patterns of miRNAs in 540 tumor tissues and found that miRNAs are differentially expressed in non-cancer and cancer tissues.…”
Section: Discussionmentioning
confidence: 99%